2022
DOI: 10.3389/fnmol.2022.843754
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Neurons in Zona Incerta Regulate Itch in Mice

Abstract: Pain and itch are intricately entangled at both circuitry and behavioral levels. Emerging evidence indicates that parvalbumin (PV)-expressing neurons in zona incerta (ZI) are critical for promoting nocifensive behaviors. However, the role of these neurons in itch modulation remains elusive. Herein, by combining FOS immunostaining, fiber photometry, and chemogenetic manipulation, we reveal that ZI PV neurons act as an endogenous negative diencephalic modulator for itch processing. Morphological data showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The sections were incubated with fluorescent secondary antibody (Alexa Fluor 488, Donkey anti-Rabbit: Thermo Fisher, A21206, 1:500; Alexa Fluor 555, Donkey anti-Mouse: Thermo Fisher, A31570, 1:500; Alexa Fluor 488, donkey anti-Mouse: Thermo Fisher, A21202, 1:500) at room temperature for 2 hours. Following previously described methods, 28 , 29 the number of GABAergic neurons in the ZI was counted bilaterally from at least six sections per animal. Counts were made from comparable sections across the full rostro-caudal extent of the ZI (rZI: two sections, dZI/vZI: two sections, rZI: two sections).…”
Section: Methodsmentioning
confidence: 99%
“…The sections were incubated with fluorescent secondary antibody (Alexa Fluor 488, Donkey anti-Rabbit: Thermo Fisher, A21206, 1:500; Alexa Fluor 555, Donkey anti-Mouse: Thermo Fisher, A31570, 1:500; Alexa Fluor 488, donkey anti-Mouse: Thermo Fisher, A21202, 1:500) at room temperature for 2 hours. Following previously described methods, 28 , 29 the number of GABAergic neurons in the ZI was counted bilaterally from at least six sections per animal. Counts were made from comparable sections across the full rostro-caudal extent of the ZI (rZI: two sections, dZI/vZI: two sections, rZI: two sections).…”
Section: Methodsmentioning
confidence: 99%
“… 30 It has extensive connectivity with other brain regions and is involved in innate instinctive behaviors, including binge eating, 31 sleeping, 32 predatory hunting, 33 , 34 defensive behavior, 35 and investigatory and seeking behavior. 36 , 37 Recent studies have also shown that the ZI is involved in pain 38 , 39 , 40 and itching, 41 which are closely related to the behavior pattern of self-grooming. However, the specific identity and neural mechanisms of the ZI related to self-grooming remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The zona incerta has also been implicated in defensive behaviors through its projections to the periaqueductal gray ( Chou et al, 2018 ), regulating cross-modality enhancement of flight through its projections to the posterior medial nucleus of thalamus ( Wang et al, 2019 ), and promoting sleep through subsets of its GABAergic neurons ( Liu et al, 2017 ). In addition, the zona incerta has been linked to other behaviors, such as mediating Pavlovian fear conditioning and anxiety ( Li et al, 2021 ; Zhou et al, 2018 ; Venkataraman et al, 2019 ), controlling predatory hunting ( Zhao et al, 2019 ), novelty seeking ( Ogasawara et al, 2022 ), itch ( Li et al, 2022 ), and neuropathic pain ( Masri et al, 2009 ; Hu et al, 2019 ; Singh et al, 2022 ). It has also been suggested as a site to alleviate essential tremor with deep brain stimulation ( Plaha et al, 2006 ) and implicated in motor control ( Mitrofanis, 2005 ).…”
Section: Introductionmentioning
confidence: 99%